Dust storm in Erbil city as a result of climatic change in Kurdistan Region Iraq - Al-Kubaisi, Qusai; Gardi, Lookman (Iraqi Journal of Science, 2024)
Dust storm in Iraq is a climatic phenomenon. Dust storm data from 1992 to 2009 and data of main climatic parameters rainfall (1942 to 2010) and air temperature (1992 to 2009) of Erbil Meteorological Station were analysed. Results show an increase of the number of suspended and rising dust as well as dust storms with time. An average of the above mentioned period of all types of dust storms is individually compared with the last five years. Again, there is a noticeable increasing of the number of storms. From the results it can be seen that the months May, June, July and August have the most frequent dust conditions while months January, February, November and December the least. The annual precipitation trend line for water years has a significant decreasing slope. While the average annual air temperature trend line has a significant increase.